2014
DOI: 10.2340/16501977-1873
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of return to work 5 years after discharge for wheelchair-dependent individuals with spinal cord injury

Abstract: Return to work after spinal cord injury was relatively high in this study, but entailed considerable changes in the employment situation, especially reduced working hours and less physically intense occupations. Rehabilitation interventions should enhance the skills and qualifications of individuals with physically-demanding pre-injury work in order to improve access to suitable jobs after spinal cord injury. Interventions should focus not only on return to work, but also on the quality of employment, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 35 publications
(56 reference statements)
2
19
1
Order By: Relevance
“…The present study furthermore provides useful information on non-pain-related influencing factors and WP in SCI. The WP rate in our study is high comparing to international studies and is in line with a relatively recent Dutch study with similar inclusion criteria showing return to work rates of 51% for ≥1 h per week and 42.6 for ≥12 h per week at 5 years following discharge from the inpatient rehabilitation [9]. A previous national study showed rates of 37% using a cross-sectional design and including participants with a shorter post-injury duration [8].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present study furthermore provides useful information on non-pain-related influencing factors and WP in SCI. The WP rate in our study is high comparing to international studies and is in line with a relatively recent Dutch study with similar inclusion criteria showing return to work rates of 51% for ≥1 h per week and 42.6 for ≥12 h per week at 5 years following discharge from the inpatient rehabilitation [9]. A previous national study showed rates of 37% using a cross-sectional design and including participants with a shorter post-injury duration [8].…”
Section: Discussionsupporting
confidence: 90%
“…WP of people with SCI, however, is low compared to the general population; work rates following SCI reported in the literature vary from 3 to 80% [4][5][6]. In studies performed in the Netherlands, WP rates of 37-67% have been reported (http://www.dehoogstraat.nl/images/products/800/eindra pportilias-definitief.pdf) [7][8][9], compared to 75% of the general Dutch population (Eurostat-tradingeconomics.com). Among factors that contribute to WP in people with SCI are non-modifiable factors such as age and gender, and it has been recommended that studies should focus on associations between modifiable factors and WP [10].…”
Section: Introductionmentioning
confidence: 99%
“…The observed employment rates for Switzerland are comparable to those from Scandinavian countries and the Netherlands averaging around 50% [16, 39], whereas LMP is significantly lower in Southern Europe and globally (37%) [5]. Employment rates of persons with SCI considerably vary by country and continent and range from 11.5% to 74.0% [16], with highest rates in Europe (51%) and lowest in North America (30%) [40] However, the interpretation of these figures is difficult as most studies do not include persons with non-traumatic SCI and use different definitions of employment (e.g., not exclusively paid employment).…”
Section: Discussionmentioning
confidence: 98%
“…13 The authors emphasized not only the importance of considering the effects of both inpatient and post discharge services when examining long-term outcomes but also identifying additional patient specific factors which can impact functional mobility across the continuum of care. 13 Functional outcomes after discharge can be influenced by sociodemographic factors 1,[14][15][16][17][18] and injury related characteristics 3,[19][20][21][22][23] including age, sex, race, cause of SCI, level and severity of neurologic impairment, and the presence of traumatic brain injury. 24 As a result of this complexity, it is important to identify specific predictors of functional outcomes.…”
Section: Introductionmentioning
confidence: 99%